Challenges and Opportunities of Digital Transformations in the Economy - ARTEMIEVAІ. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2019)
The article gives accounts of change taking place in the economy under the impact of digital transformations. The article’s objective is to highlight opportunities and threats in the operation of economic entities at various levels, caused by the development of digital economy, with outlining potential ways of effective management of this change. It is argued that digitalization is capable to radically transform the economy. Core characteristics of the digital economy are analyzed, and the most significant economic effects from digitalization are highlighted: the increasing labor productivity and employment, the increasing effectiveness of markets, the increasing quality of existing goods and services and the growing output of newly created ones. The essential principles to be met by government offices in order to maximize domestic benefits from the digital revolution are determined. Digitalization effects are analyzed at industry level, with outlining the categories of industries more and less exposed to digital transformations. At company level, opportunities and threats for individual companies, essential problems related with their adaptation to new conditions, and main features of leader companies are determined. Changes in the activities of individuals, triggered by digitalization, are described. It is concluded that while the digital economy decreases the significance of traditional production factors, qualities like flexibility, adaptability, creativity, innovativeness, orientation on knowledge and learning lifelong become crucially important.